Shelf-life and processing yields of moisture-enhanced pork loins formulated with "gourmet" salts. (May 2018) - Overholt, M.F.; Peterson, B.C.; Dilger, A.C.; Boler, D.D.
Abstract: Objectives were to determine the effects of an industry-typical (Control ) and 3 "gourmet" (Grey sea, Pink rock, and unrefinedRock ) salts on the processing yields and shelf-life of moisture-enhanced pork loins. Loins (n = 41) were injected with a brine formulated to deliver 0.32 g/100 g of salt in the final product. Twelve loins were selected from each treatment to be cut into chops to undergo 6 d of retail display. Control-injected loins had greater ( P  ≤ .01) brine uptake and retention than loins injected with Pink or Rock brines, with Grey-injected loins being intermediate. Control-injected loin chops had reduced ( P  ≤ .02) reflectance ratio compared with all other treatments and were redder ( P  ≤ .02) than Grey- and Pink-injected chops. At 3, 4, 5, and 6 d of display, control-injected loin chops had greater ( P  ≤ .05) hue angle than all other treatments. There was no difference in visual discoloration among salt treatments until 4 d, at which point loin chops injected with control brine were more ( P  < .01) discolored than the other treatments throughout the remainder of the display period. These data suggest high purity salt improves brine retention, but may reduce color stability of moisture-enhanced pork loins. Highlights: Gourmet salts reduced brine uptake and retention of brine-enhanced loins. Purified salt reduced color stability, likely due to greater concentration of NaCl. No difference in lipid oxidation or tenderness between purified and "gourmet" salts.